Use of a Video Module to Improve Faculty Understanding of the Pharmacists' Patient Care Process - Crystal Deas; Angela R Thomason; Robert M Riggs; Michael C. Thomas; Michael G. Kendrach (University of Minnesota Libraries Publishing, 2018)
Objective: To evaluate change in faculty's knowledge and perceptions after an online video module on the Pharmacists' Patient Care Process (PPCP). Innovation: An educational video module on the PPCP was developed and disseminated to full-time faculty members at Samford University, McWhorter School of Pharmacy. Voluntary and anonymous pre- and post-test assessments were evaluated and analyzed. Critical Analysis: Thirty faculty completed the pre-assessment, and 31 completed the post-assessment (73% and 75% response rates, respectively). A significant improvement in faculty perceptions was indicated by an increase in agreement with the majority (80%) of questions on attitudes toward the PPCP on the post-test. Faculty's knowledge of the introduction and assessment of PPCP within the school's curriculum was significantly increased after viewing the video module. After viewing the module, more faculty were also able to correctly identify the majority of the PPCP components and their corresponding practice activities. Next Steps: A short video module was effective at improving faculty knowledge and perceptions of the PPCP. Development of a similar faculty development module is feasible for implementation in other Schools of Pharmacy. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties. Treatment of Human Subjects: IRB exemption granted   Type: Note